Pengaruh Kepemimpinan Demokratis, Motivasi Dan Pelatihan Terhadap Kinerja Pegawai Pada Koperasi Nuansa Perkasa Kabupaten Dompu - Binti Nurlailah; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of Democratic Leadership, Motivation and Training simultaneously and partially on the performance of employees in Cooperatives in Dompu District. This research is a type of explanatory research, with a quantitative approach. The analytical method used is multiple linear regression analysis. The sample used in this study uses a saturated sample with 31 respondents.The results of this study indicate that simultaneously Democratic Leadership, Motivation and Training have a significant positive effect on Employee Performance at the Nuansa Perkasa Cooperative, Dompu Regency, and partially Democratic Leadership has a significant positive effect on Employee Performance at the Nuansa Perkasa Cooperative, Dompu Regency, Motivation has a significant positive effect on Performance Employees at the Nuansa Perkasa Cooperative, Dompu Regency, Training has a significant positive effect on employee performance at the Nuansa Perkasa Cooperative, Dompu Regency. Keywords: Democratic Leadership, Motivation, Training and Employee Performance